Tunneling Atau Value Added Dalam Strategi Merger Dan Akuisisi Di Indonesia - Mutamimah Mutamimah (Universitas Airlangga, 2009)
The purpose of this research is to analyze the effect of merger and acquisition strategy for majority and minority shareholders at Indonesia capital market. This research is important since most of company ownership structure in Indonesia is categorized concentrated structure, where its create a conflict between majority and minority shareholders. The population of the research are companies that go public in the Indonesia capital market until the year of 2006. These samples of this research consists of 35 companies, divided two groups : high and low concentrated ownership structure, that are selected based on purposive sampling method. In processes testing the hypothesis, 2 indicators were used, i.e. market indicator and accounting indicator. Event study analysis was used for market indicator, whereas multiple regression analysis was used for accounting indicator. The results show a market reaction negative and statistically significant on merger and acquisition announcement. Effect of merger and acquisition strategy on performance is negative and statistically significant. This is indicated that tunneling by majority shareholder to minority shareholders through merger and acquisition strategy, and acquisition not value added for shareholder minority.